Autocratic Legalism: the Making of Indonesian Omnibus Law - Mochtar, Zainal Arifin; Rishan, Idul (Faculty of Law, Universitas Sebelas Maret, 2022)
The Indonesian House of Representatives’ approval of the Omnibus Law on Job Creation marks a significant enhancement of the business climate and a step forward for labor market flexibility, which should, over time, improve the country’s international competitiveness. But, the Constitutional Court delivered shocking news by declaring that the omnibus Job Creation Law, is partly unconstitutional on November 2021. This study aims to reveal two things. First, procedural injustice in the making of Indonesian Omnibus Law on Job Creation. Second, the root of autocratic legalism and its prevention. The study is a doctrinal legal research with qualitative analysis. It has identified that (1) five violations of procedural justice in the making of the omnibus law reflect autocratic legalism in Indonesia; and (2) three factors contribute to the phenomenon. The three contributing factors are (i) the co-optation of the ruling party in the parliament, (ii) the violations of the law and constitution, and (iii) the undermined judicial independence. Indeed, the cartelization in political parties should be ended. Therefore, citizens need to conduct strengthened collective control. In addition, the independence of the Constitutional Court should be preserved.